Analysis of WhatsApp Groups Usage in Primary Schools during the Covid-19 Pandemic - Rahmaini Rahmaini (STAI Hubbulwathan Duri, 2021)
In the Covid-19 pandemic, distance learning is used as a method of teaching rather than learning methodologies. This research aims to investigate the implementation of distance learning through WhatsApp Group (WAG) at Private Madrasah Ibtidaiyah in Bambel Kutacane, Southeast Aceh. This research uses a qualitative approach and gathered data by conducting in-depth interviews and documentation studies (field studies). The result of the research showed that distance learning carried out by madrasah using WAG is practised in three aspects, namely (1) learning, (2) assignment and (3) assessment. Even so, socialisation and debriefing are still needed for teachers to operate online learning effectively and efficiently, both through training organised by external and internal madrasas as well as the willingness of teachers to learn self-taught.